Kajian Stilistika Dan Semiotik Dalam Cerita Watugunung - Ida Bagus Gede Paramita (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
The purpose of this research is to examine the stylistic aspects which include text schemes, message structures, and language structures in the Watugunung story and also to reveal the meaning behind the symbols of Hindu rituals in the Watugunung story. The method used in this research is qualitative method. Primary data were obtained from the Satua Watugunung text, while secondary data were obtained from books and online publications that supported the research discussion. The data collected is then selected to assist the analysis and the final step is drawing conclusions. The result of this research is that various forms of Balinese local wisdom are neatly stored in Balinese literary works. Balinese oral literature as a form of Balinese purwa literature has a role in maintaining the local wisdom of Balinese culture. specifically in Watugunung research, the stylistic elements contained in the Watugunung story are known and the meaning behind the symbols in the Watugunung story is revealed.Keywords: Stylistics, Semiotics, Watugunung